Cause analysis of gastric tube misplacement into the trachea using tetracaine gel as lubricant before gastrointestinal surgery: A case report and literature review (胃肠道术前应用丁卡因胶浆置胃管误入气管1例原因分析并文献复习) - HE Shu (何姝); YU Chunguang (于春光); LI Jiaji (李佳霁); CUI Kaiyue (崔凯月); CHEN Kun (陈坤); DI Xiaowei (狄晓玮) (中西医结合护理)
Gastric tube placement is a common clinical procedure. During the catheterization process, the gastric tube may enter the trachea by mistake, presenting symptoms such as choking, dyspnea, cyanosis and so on. Occasionally, patients have atypical symptoms, which are easily ignored in clinical practice, bringing great safety risks to the operation. This paper reported a case of gastric tube misplacement into the trachea using tetracaine gel as lubricant before gastrointestinal surgery, analyzed the causes and summarized the preventive and nursing measures, and reviewed the new methods, new techniques and relatively rare complications of gastric tube placement. The lubricant with anesthetic effect should be used carefully when placing gastric tube. The application of new technology can improve the success rate of gastric tube placement. (安置胃管是常见的临床操作。在置管过程中, 胃管可能会误入气管, 表现为呛咳、呼吸困难、发绀等症状, 偶有患者症状不典型, 存在安全隐患。现报告1例应用丁卡因胶浆置管过程中胃管误入气管且无典型症状的病例, 分析原因并总结预防护理措施, 并结合文献对安置胃管的新方法、新技术及相对罕见的并发症进行总结。 安置胃管时使用带有麻醉作用的润滑剂需谨慎, 新技术的应用可提高安置胃管的成功率。)